1991
DOI: 10.1149/1.2085661
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonically Induced Cavitation Studies of Electrochemical Passivity and Transport Mechanisms: I . Theoretical

Abstract: High intensity ultrasound causes the formation of cavitation bubbles which collapse in a manner that, in the presence of a solid surface, form high velocity fluid microjets directed toward the surface. The intense fluid agitation at surfaces in a focused ultrasound field enhances transport of momentum, heat, and mass and influences the behavior and integrity of surface films on metal electrodes. A mathematical model is proposed to determine the reaction and transport between liquid microjets and a reactive sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 6 publications
2
26
0
2
Order By: Relevance
“…19 Perusich and Alkire investigated the effect of a focused ultrasonic field on mass transport to an electrode. 20, 21 Dewald and Peterson employed a 20 kHz ultrasonic source and constructed a hydrodynamically modulated electrode by the use of a pulsed ultrasonic field. 22 Zhang and Coury demonstrated that high pseudo-steady-state mass transfer with impressive mass transfer rates could be achieved by positioning an electrode within the plume of an operating ultrasonic horn.…”
Section: Introductionmentioning
confidence: 99%
“…19 Perusich and Alkire investigated the effect of a focused ultrasonic field on mass transport to an electrode. 20, 21 Dewald and Peterson employed a 20 kHz ultrasonic source and constructed a hydrodynamically modulated electrode by the use of a pulsed ultrasonic field. 22 Zhang and Coury demonstrated that high pseudo-steady-state mass transfer with impressive mass transfer rates could be achieved by positioning an electrode within the plume of an operating ultrasonic horn.…”
Section: Introductionmentioning
confidence: 99%
“…This effect can contribute significantly towards improvement of mass transfer. [43][44][45][46][47][48][49] However, micro-jetting can also cause pitting and erosion to the electrode surface during electrodeposition. 43,50 Additionally, there remains a concern regarding US agitation, which itself is generated by cavitation, which may increase the number of gas bubbles.…”
Section: Ultrasonic Agitationmentioning
confidence: 99%
“…A aplicação do ultrasom a uma solução pode aumentar drasticamente o transporte do material eletroativo à superfície eletródica. Muitos autores têm se dedicado a desenvolver descrições quantitativas e à identificação dos processos físicos envolvidos 18,19,[61][62][63][64] . Na Figura 2a estão apresentados voltamogramas cíclicos típicos da reação do par reversí-vel Fe(CN) 6 4-/3-sobre um eletrodo de DDB em meio de KCl 0,1 mol L -1 na ausência (I) e na presença do ultra-som (II).…”
Section: Influência No Transporte De Massaunclassified
“…Os efeitos da aplicação do ultra-som no transporte de massa são complexos e têm sido propostos teoricamente 18 , empiricamente [19][20][21] e por modelos aproximados de simulação 22,23 . Importantes aspectos da sonoeletroquímica foram relatados por Walter e Phull 24 mostrando a quantificação de processos sonoeletroquímicos.…”
Section: Introductionunclassified